The role of material fabric in concrete under uniaxial compression. (September 2021) - Ghosh, Subha; Deb, Arghya
Abstract: The paper extends the formal structure of the fabric based analysis of cohesion-less granular materials to cemented granular materials such as concrete. The stress-fabric and strain-fabric relationships are derived, and both are seen to be sensitive to particle angularity and maximum particle size. The contributions of the isotropic and anisotropic parts of the micro structural stress and strain are identified and a recently developed discrete element capability used to investigate their separate contributions to the macro behaviour in uniaxial compression. The anisotropic part of the micro-structural stress plays a dominant role in determining the peak strength. However, post peak ductility is largely controlled by the isotropic part. Remarkably fabric anisotropy, which depends strongly on particle angularity, is seen to result in higher hydrostatic pressures. This strengthens the "internal confinement mechanism" and accounts for the superior strength of specimens with angular aggregates observed in experiments.